Development of a Leak Detection and Localization System Based on Parametric Models - MEFTAH Sabir (University of M'Sila, 2025)
In the core of this thesis, three methodologies were developed to address water leakage in the water distribution networks (WDNs). The first one was conducted on the development and the demonstration of a mathematical model for leak localization. It depends on the laws of fluid mechanics. Two crucial parameters that can’t be calculated, we should optimize. For that we use an evolutionary metaheuristic method, which is the biogeography-based optimization (BBO) method that has three main stages (migration, mutation, and an optional one, which is elitism). After obtaining the two unknown parameters by optimization and using the physical characteristics of the transportation pipe (length, diameter, etc.), the flow rate measurements at the two ends of the pipe, we can define the exact position of the leak. With the development of technology and the transition from the analog world to the digital world, as well as the exploitation of signal processing functions, correlators have emerged. The latter rely for their operations on two acoustic sensors placed on fire hydrants at a distance of 500 m to 1 km. The microphones or hydrophones not only transmit the leak signals but also pick up surrounding noises. The received radio frequency signals will be subjected to signal processing functions to confirm the presence of the leak and its location relative to one of the sensors. Their disadvantages lie in false alarms caused by environmental noise, thus causing the destruction of infrastructure. In addition, they require a qualified workforce. The researchers are oriented to exploit the vibration sensors and the analysis of the transient phenomena that occur. Road traffic and daily work share noises that are added to the useful signal, always causing anomalies in the infrastructure. The problem is to think of an effective and inexpensive way to solve the problem of leaks. The second contribution addresses noise and false alarms in a pressure leak detection system. Using a custom-built laboratory prototype, pressure signals were collected and denoised with a Savitzky-Golay filter. Leak localization was achieved through time-difference calculations of signal arrivals at high-precision transmitters, validated against known leak positions in a zigzag-shaped HDPE pipe network. The third contribution enhances the detection process using a larger experimental prototype. Pressure signals from leaks of varying sizes were processed using discrete wavelet transform (DWT) and Donoho thresholding for noise removal. Reconstructed signals were analyzed for quality metrics such as SNR, NCC, and MSE. Time differences in signal arrivals, combined with pressure wave velocity, allowed accurate leak localization, validated across diverse leak scenarios. This research advances the precision and robustness of leak detection methodologies, providing practical, cost-effective solutions for WDN maintenance and management.
2025
Keywords: WDNs; Leak Detection; Localization; BBO; Signal Processing; DWT; Pressure signals.; WDNs ، كشف التسربات، تحديد الموقع، BBO ، معالجة الإشارة، DWT ، إشارات الضغط.